IMPROVING TEACHERS' ABILITY IN PREPARING ENGLISH COMPETENCIES THROUGH TOEFL FOR PREPARATION OF SCHOLARSHIP REQUIREMENTS - Abadi, Ayuliamita; Sakunti, Sri Ramdayeni; Pratama, Aryawira; Rozal, Edi; Monalisa, Monalisa; Tartila, Tartila; Zurnelli, Netti; Zuhriyah, Latifatul (LPPM Univ. Ibn Khaldun Bogor, 2024)
This community service program aimed to enhance the English language proficiency of teachers in Kabupaten Tanjung Jabung Timur through TOEFL training as a preparation for scholarship applications. Using the Asset-Based Community Development (ABCD) approach, the program involved 26 teachers from various schools, including classroom teachers, non-English subject teachers, and English teachers. Conducted over seven sessions, the program began with a pre-test to evaluate participants' initial abilities and concluded with a post-test using TOEFL Prediction to measure progress. The pre-test results indicated that participants' TOEFL Prediction scores ranged from 300 to 370, highlighting the need for structured training. Through interactive methods, group discussions, simulations, and mentoring, participants improved their understanding of TOEFL material and test-taking strategies. The post-test results demonstrated significant progress, with scores ranging from 400 to 460. Participants also gained confidence in facing the TOEFL exam and understanding how to integrate English learning into their teaching practices. The program successfully fostered collaboration between educational institutions, local governments, and communities, ensuring its sustainability. Overall, this initiative not only improved teachers' English proficiency but also contributed to enhancing the quality of education in Kabupaten Tanjung Jabung Timur, preparing teachers and Participants alike for better educational opportunities.